The impact of co-production on frontline accountability: the case of the conciliation service. (March 2016) - Tuurnas, Sanna; Stenvall, Jari; Rannisto, Pasi-Heikki
Mixing of roles between professionals, volunteers and service users creates a new, complex environment in which to produce and deliver public services. In this kind of environment, the issues of accountability become ever more important. This article presents a qualitative case study of co-production between volunteers and professionals in the legally regulated restorative justice services in Finland. Theoretically, we draw together the concept of citizen co-production with the literature on street-level bureaucracy and accountability. As a result of the study, we can say that co-production between volunteers and professionals increases accountability ties. In particular, the meaning of process-centred accountability is salient in horizontal accountability relations. Thus, co-production as a governance arrangement changes the working culture of public service professionals. In the new partnerships, although not entirely horizontal, we can recognize a seed for cultural change for professionalized public service organizations. Points for practitioners: In this article we have researched co-production between professionals and volunteers in a legally regulated public service, the conciliation service, examining the perceptions of accountability in the frontline practices. The results show that the process-centred nature of the co-produced services leaves less room for discretion and the application of rules by individual street-level workers. Furthermore, as the service users do not consider volunteers to be part of the authority, co-production might be smoother. This is significant especially in the social services, where the clients per se are not necessarily motivated to co-produce, but where co-production would be essential for achieving effective service outcomes.